2013
DOI: 10.1371/journal.ppat.1003586
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Novel Glutamate-Gated Chloride Channel Subunits from Schistosoma mansoni

Abstract: Cys-loop ligand-gated ion channels (LGICs) mediate fast ionotropic neurotransmission. They are proven drug targets in nematodes and arthropods, but are poorly characterized in flatworms. In this study, we characterized the anion-selective, non-acetylcholine-gated Cys-loop LGICs from Schistosoma mansoni. Full-length cDNAs were obtained for SmGluCl-1 (Smp_096480), SmGluCl-2 (Smp_015630) and SmGluCl-3 (Smp_104890). A partial cDNA was retrieved for SmGluCl-4 (Smp_099500/Smp_176730). Phylogenetic analyses suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 98 publications
(134 reference statements)
4
52
0
Order By: Relevance
“…Schistosomes and other platyhelminths are typically not sensitive to macrocyclic lactones [53, 54] (though see [55]), which could suggest an absence of GluCl channels in these organisms. However, exciting recent work [56] has demonstrated that schistosomes in fact do express GluCl channel subunits, but that these subunits are phylogenetically distinct from those of other invertebrates, including nematodes, arthropods, and molluscs. When expressed in Xenopus oocytes, schistosome GluCl subunits form functional L-glutamate-gated, Cl − -permeable channels.…”
Section: Glutamate-gated Chloride Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schistosomes and other platyhelminths are typically not sensitive to macrocyclic lactones [53, 54] (though see [55]), which could suggest an absence of GluCl channels in these organisms. However, exciting recent work [56] has demonstrated that schistosomes in fact do express GluCl channel subunits, but that these subunits are phylogenetically distinct from those of other invertebrates, including nematodes, arthropods, and molluscs. When expressed in Xenopus oocytes, schistosome GluCl subunits form functional L-glutamate-gated, Cl − -permeable channels.…”
Section: Glutamate-gated Chloride Channelsmentioning
confidence: 99%
“…Macrocyclic lactones also appear to interact with nematode GABA-gated channels [57], and there is some evidence that the cyclooctadepsipeptide PF1022A (see below) binds to and interacts with nematode GABA receptors [59], though electrophysiological experiments suggest that it does not act as a GABA agonist [60]. Surprisingly, schistosomes do not appear to have genes for GABA-gated channels [56]. …”
Section: Gaba-gated Chloride Channelsmentioning
confidence: 99%
“…Invertebrate genomes, in contrast, encode a greater assortment of channel types with a wider range of ligand specificities and ligand-ion combinations than those found in vertebrates (Dent, 2006). In addition to the nicotinic acetylcholine and GABA receptors found in vertebrates, invertebrate genomes encode anion-selective acetylcholine (Putrenko et al, 2005;van Nierop et al, 2005), histamine (Gengs et al, 2002;Zheng et al, 2002), glutamate (Dent et al, 1997;Dufour et al, 2013;Kehoe et al, 2009), serotonin (Ranganathan et al, 2000), dopamine (Ringstad et al, 2009), tyramine (Ringstad et al, 2009) and pH (Mounsey et al, 2007;Schnizler et al, 2005) channels, as well as cation-selective GABA (Gisselmann et al, 2004) and proton (Beg et al, 2008) channels. Moreover, multiple putative invertebrate pLGICs have been identified that cannot be assigned to any neurotransmitter family based on sequence homology.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds were: the antimalarial drug mefloquine (MFQ) [27]; the antihelmintic Ivermectin (IVM) [28, 29]; the bromodomain inhibitor JQ1 [30]; and the reference drug praziquantel (PZQ). The positive and negative controls average absorbance values were used to calculate parasites viability.…”
Section: Resultsmentioning
confidence: 99%